Music Competitions within the Internationalization of an Arts University : Case Study of International Maj Lind Piano Competition - Niemensivu, Outi (Taideyliopiston Sibelius-Akatemia, 2018)
The aim of this study is find out how classical music competitions work within the internationalization of an arts university. The internationalization of the University of the Arts Helsinki is studied through the International Maj Lind Piano Competition organized by the Sibelius Academy. The instrumental case study is based on eight interviews with representatives of the top management of the university, the competition organization and the competitors forming three stakeholder groups. Research on internationalization of higher education institutions serves as the theoretical framework. The analysis concentrates on three themes as seen by the stakeholder groups: benefits to the stakeholders, methods to increase the appeal of the competition, and organizational and governance challenges. The results suggest that the International Maj Lind Piano Competition supports the internationalization efforts of the University of the Arts Helsinki, but not to its full potential. A clearly defined internationalization strategy combined with a cyclical process orientation with expressed commitment and clearly defined internationalization goals offer fruitful possibilities to utilize the competition for the internationalization of the university. This study contributes to the research of HEI internationalization and arts management from the viewpoint of arts universities and international competitions. Concrete examples in the study bring fresh perspectives to the representatives of arts universities and international music competitions.
Keywords: taidehallinto; kilpailut; piano; kansainvälisyys; fi=taidehallinto|sv=Arts Management|en=Arts Management|